BAGAIMANA MAHASISWA MEMBACA LEBIH PRODUKTIF? - Sutanto, Agus (UNIVERSITAS MUHAMMADIYAH METRO, 2011)
Reading is an important activity for a student to complete his studies. Nevertheless there are still many students not have good reading skills. A good reading would be more productive and effective produce quality students. Various methods have been formulated by experts, which is best depending on the student to choose which best suits his interests.Kata kunci:: aktivitas, membaca, metode